Hubungan Intensitas Komunikasi Virtual Dengan Komitmen Pada Pernikahan Jarak Jauh - Mirna Sulfitri; Basti; Muh Nur Hidayat Nurdin (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This study aims to determine the role of virtual communication intensity with commitment to long-distance marriage. Data were collected using a questionnaire containing a virtual communication intensity scale and a commitment scale. The number of subjects in this study 103 subjects who are undergoing long-distance marriage. This study uses quantitative methods and uses data analysis techniques Spearman Rho correlation. The results of this study indicate that there is a significant positive relationship between the intensity of virtual communication and commitment to long-distance marriage with a correlation coefficient of r = 0.214 with p = 0.030 (p <0.05). These results indicate that there is a significant positive relationship between the virtual communication intensity variable and commitment to long-distance marriage. This means that the higher the virtual communication, the higher the commitment, and vice versa, the lower the virtual communication intensity, the lower the commitment. So it can be stated that there is a relationship between the intensity of virtual communication with commitment to long-distance marriage